A liberatory pedagogy for non-native teachers of english - Cakcak, Yasemin Tezgiden (Ankara : Ankara Üniversitesi Eğitim Bilimleri Fakültesi, 2018)
Native English speaking teacher of English/non-native English speaking teacher of English (NEST/NNEST) inequity has been a well-documented reality in the foreign language education field. Interpreting the dichotomy of NEST/NNEST from Freire's theoretical perspective, this article provides insights into the internalization of native speakerist ideology by large numbers of non-native teachers of English. Using Freire's understanding of the relationship between the oppressor and the oppressed, this article argues that non-native teachers of English are divided beings: they are both themselves and the consciousness of the native speaker they internalized. Following Freire's liberatory pedagogy, this article suggests a dialogical problem-posing education for overcoming NEST-NNEST inequity in English language teacher education in Turkey.
Keywords: English teacher education